Influence of X-Ray Radiation on Historical Paper - Zippert, Patrick; Seuret, Mathias; Maier, Andreas; Hausotte, Tino (11th Conference on Industrial Computed Tomography, 2022)
Historical books are often so fragile that they cannot easily be opened in order to read the contents without damaging them. Current research shows, that industrial X-ray computed tomography (CT) can be used to examine closed historical manuscripts. However, the effect of X-rays on ancient paper has rarely been studied, making it difficult to assess the impact of CT measurements on fragile historical manuscripts in terms of additional destruction. To address this problem, various types of paper were exposed to high levels of X-ray radiation in order to examine them for change in optical properties. The investigations showed increasing yellowing due to the increased radiation energy. However, the severity of the yellowing is strongly dependent on the composition of the paper.<br
Keywords: Historical documents; CT measurement side effects; radiation damage